Mechanical, electronic and catalytic properties of 2H–1T′ MoS2 heterointerfaces. Issue 41 (18th October 2022) - Huang, Xiangru; Chang, Yuan; Qiu, Shi; Liu, Hongsheng; Shymanski, Vitali; Gao, Junfeng
Abstract : Compared with the 2H and 1T′ MoS2 phases, 2H–1T′ MoS2 in-plane heterointerfaces exhibit a much better catalytic activity for the hydrogen evolution reaction, which can be further tuned using strain engineering. Abstract : Using first-principles calculations, we comprehensively explored the influence of 2H–1T′ heterointerfaces in molybdenum disulfide (MoS2 ) on the mechanical, electronic and catalytic properties of MoS2 . The S-orientated interfaces, including interfaces with interstitial S or S vacancies, were adopted as samples. All the heterostructures show a smaller yield stress than 2H and 1T′ MoS2, and fractures always occur at the interface. The heterostructures are either metallic or half-metallic. Some of the heterointerfaces show great catalytic ability for the hydrogen evolution reaction (HER). In particular, the Gibbs free energy of H adsorption is as low as −0.028 eV for the S-LU-sint structure. Moreover, a small strain of 4% can improve the HER catalytic activity for several heterostructures. Our results show that 2H–1T′ MoS2 heterointerfaces are potential catalysts for the HER.